Synergy of Competence, Placement, and Job Satisfaction in Encouraging the Performance of District Apparatus - Sutianingsih; Lega Hidayating Edi (Journal of Islamic Enterpreneurship and Management, 2025)
Employee performance is a crucial factor for the success of an organization. To achieve optimal performance, several factors need to be considered, including employee competence, job placement, and job happiness. This study focuses on analyzing the relationship between these variables and employee performance in the Mondokan District area, Sragen Regency. The main objective of this study is to identify and analyze the relationship between employee competence, job placement, and job happiness with employee performance in Mondokan District, Sragen Regency. This study uses a quantitative approach with a cross-sectional study design. The population of this study consisted of 45 workers in Mondokan District, Sragen Regency. The sampling technique used is saturated sampling, where the entire population is sampled. Therefore, the sample of this study amounted to 45 employees. Primary data were collected directly using questionnaires as research instruments. Data analysis was carried out using multiple regression analysis through SPSS software. The results of the study showed a positive and statistically significant relationship. It was found that employee competencies have a positive and significant relationship to their performance. In addition, job placement also has a positive and significant effect, and job happiness has been shown to be positively correlated with increased employee productivity.